Finis coronat opus Festschrift für Walter Kroll zum 65. Geburtstag - Bockholt, Volker; Freise, Matthias; Lehfeldt, Werner; Meyer, Peter (Universitätsverlag Göttingen, 2006)
In the 24 contributions of this commemorative publication companions, colleagues and friends of the Göttingen Slavonic and Literary scholar Walter Kroll honor his 65th Birthday. Its thematic diversity reflects the breadth of the academic interests and research areas of the honoured. In addition to the essays on aspects of the Bulgarian, Croatian, Lachian, Polish, Russian and Czech literature, the volume contains also works regarding the following areas: cultural studies, literary theory, modern history, Russian philosophy, micro literary language research, language, personal names research, lexical semantics, historical and comparative linguistics . Some cheerful and a lyrical contribution, plus a list of publications round off the volume.